2019
DOI: 10.1002/sctm.18-0192
|View full text |Cite
|
Sign up to set email alerts
|

Early Intravenous Infusion of Mesenchymal Stromal Cells Exerts a Tissue Source Age-Dependent Beneficial Effect on Neurovascular Integrity and Neurobehavioral Recovery After Traumatic Cervical Spinal Cord Injury

Abstract: Localized vascular disruption after traumatic spinal cord injury (SCI) triggers a cascade of secondary events, including inflammation, gliosis, and scarring, that can further impact recovery. In addition to immunomodulatory and neurotrophic properties, mesenchymal stromal cells (MSCs) possess pericytic characteristics. These features make MSCs an ideal candidate for acute cell therapy targeting vascular disruption, which could reduce the severity of secondary injury, enhance tissue preservation and repair, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 116 publications
1
13
0
Order By: Relevance
“…It is likely that all these events occur simultaneously at 24 and 48 h after injury contributing to the highly variable reports in the literature. Immunohistochemistry revealed that in injured animals, there were areas of neurofilament accumulation (NF200), but not accompanied with maintenance of axonal length, administration of HUCPVCs was associated with preservation of axonal length and less compaction of NF200, and is consistent with other studies [58]. These data suggest that HUCPVCs can support axonal health and integrity that maintains proper signaling after injury and preserve functional outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…It is likely that all these events occur simultaneously at 24 and 48 h after injury contributing to the highly variable reports in the literature. Immunohistochemistry revealed that in injured animals, there were areas of neurofilament accumulation (NF200), but not accompanied with maintenance of axonal length, administration of HUCPVCs was associated with preservation of axonal length and less compaction of NF200, and is consistent with other studies [58]. These data suggest that HUCPVCs can support axonal health and integrity that maintains proper signaling after injury and preserve functional outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…It is estimated that there are approximately 11,000 new patients with SCI in America each year, and currently, there are approximately 250,000 people with SCI (Qin et al, 2018;Hall et al, 2019;Liu et al, 2019). SCI is mostly caused by trauma, including the primary mechanical injury due to a rapid direct compression and contusion of the cord, and the subsequent secondary pathophysiological changes, such as edema, ischemia, apoptosis, autophagy, and oxidative stress, which usually lead to a permanent neurological impairment (Kang et al, 2018;Alizadeh et al, 2019;Vawda et al, 2019). The primary injury is in fact mostly unavoidable.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, transplantation of MSCs following SCI has shown protective effects to local vasculature (Matsushita et al, 2015;Morita et al, 2016;Vawda et al, 2019). Additionally, MSCs are also capable of promoting neuroprotection and modulation of the immune response toward a more regenerative-prone environment, which broadens the range of their effect and make them a promising candidate to treat SCI (Novikova et al, 2011;Spejo et al, 2013;Ribeiro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%